Relationship of maximal leg strength and sprinter's stride length - Tuttle, W. M.; Finch, A. E.; Ginter, K.; Kuhlman, J. (ISBS Proceedings Archive (Michigan), 2019)
Relationships between maximal squat strength, peak velocities, and relative stride lengths were examined in male and female collegiate sprinters during a 60m sprint. Runners were videotaped at 120 Hz. and stride lengths, and peak velocities were calculated using the Ariel APAS software. Sprinters` 1-RM squat strengths and leg lengths were measured. A high correlation of r=.904, (p=.09) was found between the male sprinters` leg strength and relative stride length, and the females had a low non-significant r=.515. A high significant correlational relationship of r=.988 (p=.04) was found for male leg strength and sprint velocity, and the females had a non-significant correlation r=.074. Male sprinter leg strength was a significant training factor influencing relative stride length, and sprinting velocity. While female leg strength was a not a factor for the relative stride length, and peak velocity.